A78 IMPACT OF IMPLEMENTING A RAPID ACCESS CLINIC IN A HIGH-VOLUME INFLAMMATORY BOWEL DISEASE CENTER: ACCESSIBILITY, REASOURCE UTILISATION AND OUTCOMES - Nene, S (J Can Assoc Gastroenterol, 2019)
BACKGROUND: Emergency situations in inflammatory bowel diseases (IBD) put significant burden on the patient and healthcare system as well. AIMS: We aimed to prospectively measure indicators of quality-of-care, after implementation of a new rapid access clinic (RAC) at the McGill University Health Centre (MUHC) tertiary care IBD center. METHODS: The RAC provides patients an opportunity to be evaluated by IBD specialists urgently without having to present to the emergency department. RAC was structured by providing an emergency contact email address to the patients, with a specific document explaining the pertinent symptoms that merit utilization of this access avenue. Each email was read and reviewed by a specialized IBD nurse or physician. Patient access, resource utilization and outcome parameters were collected from MUHC IBD Center Rapid Access clinic including consecutive patients who contacted the RAC via email between July 2017 and September 2018. RESULTS: 261 patients (44.1% men, mean age: 39 years, CD: 64% [L3: 46.2%, B2–3: 31.8%], UC: 32% [extensive colitis: 56.6%], biological therapy: 61.6%, previous surgery: 20.4%) were included. 85.7% of requests were deemed appropriate for a rapid appointment. The reason for RAC appointment was potential disease flare in 62.5% of patients. The median time to RAC visit was 3 days (IQR: 1–6 days) from the first point of contact (email/phone) by the patient. Patients had a fast track evaluation with optimized resource utilization in the majority of cases. CRP and fecal calprotectin were the most common measures of disease severity performed, 85.2% and 62.5%, respectively. Clostridium difficile stool test and stool culture test were performed in 43.8% and 42.4% of the patients. The frequency of colonoscopy and flexible sigmoidoscopy following the RAC visit were 22.9% and 6.7%. Only a minority of patients underwent CT (7.1%) and MR (1%) imaging. A change in therapy occurred in 57.0% of patients. Within 30 days from the index visit, 21 patients (19 patients with IBD related symptoms) required ER. 8 ER visits were initiated during the RAC visit and resulted in admission, 7 other patients had unplanned ER visit due to continuous IBD activity. Only 5 patients who were screened by the RAC physician and deemed not to require an urgent consultation presented at the ER (unplanned ER visit rate were 1.8%, no patient required admission). CONCLUSIONS: Implementation of an RAC improved healthcare delivery by avoiding unnecessary ER visits and by increasing access to an IBD center. Patients had a fast track evaluation with optimized resource utilization. Data presented here can serve as example for a more optimal cost utilization for future IBD centers. FUNDING AGENCIES: McGill Department of Medicine CAS Research Support